10 Psychiatric Co-morbidities and Tendencies in Patients with Non-Ischaemic heart Failure (NIHF) – A Large Observational Cohort Study Spanning 14 Years. (3rd June 2016) - Rasoul, D; Wong, Sam; Chandran, Suresh; Uppal, Hardeep; Sarma, Jaydeep; Potluri, Rahul
Abstract : Introduction: Studies have shown that one in four psychiatric patients also suffer from a cardiovascular co-morbidity, and in recent years the links between cardiovascular disease and psychiatric conditions have been on the rise. We decided to investigate the prevalence of psychiatric co-morbidities and tendencies in patients with NIHF over a 14 year period. Methods: We compiled an anonymous database of adult patients diagnosed with NIHF across 7 hospitals in the North of England, UK, during 01/01/2000 to 31/03/2013. We analysed the data for prevalence of psychiatric co-morbidities such as; anxiety disorder, schizophrenia, depression etc. and for tendencies such as substance abuse and suicide attempts. We traced our patients with the ACALM (Algorithm for Co-morbidities, Associations, Length of Stay and Mortality) study protocol, which uses ICD-10 and OPCS-4 codes to allocate patients for statistical analysis using SPSS Version 20.0. Results: Between the years 2000–2013, 929, 552 patients were admitted, 958 (0.1%) of which had NIHF. The majority of our patients where male (68%), had a mean age of 54.9 years ± 13.9 years, and had a Caucasian background (77%). Of these 958 patients, 8.1% (n = 78) had a psychiatric co-morbidity; depression and schizophrenia where most prevalent. Depression however, seems to more prevalent in dilated cardiomyopathy (DCM) as opposed to hypertrophic cardiomyopathy (HCM). 10.3% (n = 99) suffered from substance abuse, made up mainly by alcohol and tobacco abuse. 2 of our patients (0.2%) where admitted following suicide attempts. Conclusion: It remains debatable whether these psychiatric conditions and tendencies represent a causative or correlative link. Studies exists to lend evidence to both claims. We did however find a steady increase in tobacco and alcohol abuse, and the diagnosis of depression in relation to our cohort during our 14-year period. We found that almost one in ten (8.14%) patients with NIHF suffer from psychiatric co-morbidity and that one in ten (10.33%) abuse some form of substance alongside their cardiac condition. Thus, a holistic approach to patients with NIHF should be adopted, and this approach would fall short if it did not explore patient's use of recreational drugs, suicidal intent and psychiatric wellbeing.